2012
DOI: 10.1186/1742-2094-9-151
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune challenges trigger and drive Alzheimer-like neuropathology in mice

Abstract: BackgroundAlzheimer’s disease (AD) is the most prevalent form of age-related dementia, and its effect on society increases exponentially as the population ages. Accumulating evidence suggests that neuroinflammation, mediated by the brain’s innate immune system, contributes to AD neuropathology and exacerbates the course of the disease. However, there is no experimental evidence for a causal link between systemic inflammation or neuroinflammation and the onset of the disease.MethodsThe viral mimic, polyriboinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
333
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(351 citation statements)
references
References 66 publications
14
333
3
1
Order By: Relevance
“…16 More recently, we demonstrated that upon second immune stimulation with PolyI:C in adulthood, prenatally challenged animals developed an AD-like pheno type. 17 The ageing-associated progression of disease in these mice was in striking similarity to that described in patients with AD. 2 In addition, systemic immune challenge in adult transgenic AD mice led to a strong aggravation of the AD-like pathology, 17 in agreement with the observation that both acute and chronic inflammation are associated with an increase in cognitive decline in patients with AD.…”
Section: Inflammation Hypothesis Of Admentioning
confidence: 48%
“…16 More recently, we demonstrated that upon second immune stimulation with PolyI:C in adulthood, prenatally challenged animals developed an AD-like pheno type. 17 The ageing-associated progression of disease in these mice was in striking similarity to that described in patients with AD. 2 In addition, systemic immune challenge in adult transgenic AD mice led to a strong aggravation of the AD-like pathology, 17 in agreement with the observation that both acute and chronic inflammation are associated with an increase in cognitive decline in patients with AD.…”
Section: Inflammation Hypothesis Of Admentioning
confidence: 48%
“…In support of such a view is the observation that upon neuronal injury, Reelin expression is up regulated in Schwann cells (Panteri et al, 2006) and that Reelin knock-out mice show impaired peripheral nerve regeneration (Lorenzetto et al, 2008). It would be highly relevant, therefore, to check in the adult brain if oligodendrocytes, which express Reelin in vitro (Siebert and Osterhout, 2011) Importantly, we were recently able to demonstrate that a viral-like prenatal immune challenge predisposes the offspring to develop an AD-like phenotype, which is induced if the challenge is repeated for a second time during adulthood (Krstic et al, 2012a). In these prenatally challenged mice, the loss of Reelin expressing cells (Meyer et al, 2008, Knuesel et al, 2009 coincided with an increase in APP production and cleavage, Tau hyperphosphorylation and missorting, as well as cognitive deficits (Krstic et al, 2012a).…”
Section: And Promotesmentioning
confidence: 97%
“…It would be highly relevant, therefore, to check in the adult brain if oligodendrocytes, which express Reelin in vitro (Siebert and Osterhout, 2011) Importantly, we were recently able to demonstrate that a viral-like prenatal immune challenge predisposes the offspring to develop an AD-like phenotype, which is induced if the challenge is repeated for a second time during adulthood (Krstic et al, 2012a). In these prenatally challenged mice, the loss of Reelin expressing cells (Meyer et al, 2008, Knuesel et al, 2009 coincided with an increase in APP production and cleavage, Tau hyperphosphorylation and missorting, as well as cognitive deficits (Krstic et al, 2012a). This is in agreement with the observations of cognitive decline in aged rats correlating with reduced Reelin expression in the entorhinal cortex (Stranahan et al, 2011a), recently confirmed by the findings of impaired spatial memory following experimental interference with Reelin signaling in the same area (Stranahan et al, 2011b).…”
Section: And Promotesmentioning
confidence: 99%
“…Although the majority of inflammation in AD is attributed to glia dysfunction, especially in microglia and astrocytes, systemic inflammation shows a strong association with AD, as shown by an interesting experiment: Under systemic immune challenge by the viral mimic polyriboinosinic–polyribocytidilic acid, mice show sporadic AD phenotypes including Aβ plaques and altered Tau phosphorylation (Krstic et al, 2012). In human, there are some similar association studies: Obesity increases the likelihood of systemic inflammation (Almond, Edwards, Barclay, & Johnston, 2013), and white‐fat tissue has a high percentage of activated macrophages secreting proinflammatory cytokines (Bastard et al, 2006); thus, it is not surprising to find that midlife obesity is a risk factor for AD (Whitmer et al, 2008).…”
Section: Systems Level Events In Aging and Admentioning
confidence: 99%